2014
DOI: 10.1089/jop.2014.0010
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Intravitreal Implant in Vitrectomized Versus Nonvitrectomized Eyes for Treatment of Patients with Persistent Diabetic Macular Edema

Abstract: In this study, the clinical findings were similar between nonvitrectomized and vitrectomized eyes. Intravitreal treatment with a DEX implant safely reduced DME and improved visual acuity in both groups. No statistically significant differences were found between the 2 groups regarding FT and BCVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 54 publications
(60 reference statements)
3
62
0
Order By: Relevance
“…In this regard, a DEX implant that slowly releases the total dose of DEX over a series of months after insertion into the eye may be a useful option for vitrectomized eyes. Medeiros et al [25] demonstrated similar effectiveness of a DEX implant in nonvitrectomized and vitrectomized eyes after the administration of a 0.7-mg DEX implant. A clinical trial known as the CHAMPLAIN study evaluated 55 patients with treatment-resistant DME and a history of previous vitrectomy [9].…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, a DEX implant that slowly releases the total dose of DEX over a series of months after insertion into the eye may be a useful option for vitrectomized eyes. Medeiros et al [25] demonstrated similar effectiveness of a DEX implant in nonvitrectomized and vitrectomized eyes after the administration of a 0.7-mg DEX implant. A clinical trial known as the CHAMPLAIN study evaluated 55 patients with treatment-resistant DME and a history of previous vitrectomy [9].…”
Section: Discussionmentioning
confidence: 97%
“…Drug clearance from the vitreous has been demonstrated to be increased after vitrectomy, limiting the treatment options for macular edema in vitrectomized eyes [16][17][18] . Sustained-release corticosteroids have the potential to reduce the need for frequent intraocular injections in vitrectomized eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone (DEX) intravitreal implant (Ozurdex ® , Allergan, Inc., Irvine, CA, USA and Allergan Pharmaceuticals, Ireland) has been shown to reduce central retinal thickness (CRT) and improve best-corrected visual acuity (BCVA) in patients with macular edema of various etiologies including noninfectious uveitis, diabetes mellitus, and retinal vein occlusion [8][9][10][11][12][13][14][15] . Over the past years, several small case series and anecdotal reports have strengthened the hypothesis that intravitreal steroid implants may be effective in the treatment of refractory CME in vitrectomized eyes [16][17][18][19][20] . However, to date there are no large studies evaluating the efficacy and safety of intravitreal sustained-release steroid implants for the management of CME following vitrectomy and membrane peeling.…”
mentioning
confidence: 99%
“…It is important to note that this treatment seems to be as effective in vitrectomized as nonvitrectomized patients [15], which might represent a benefit for this group of patients in which vitrectomy is frequently performed during the progression and follow-up of the disease.…”
Section: Discussionmentioning
confidence: 99%